The complete mitochondrial genome of sponge Halichondria sp. (Demospongiae, Suberitida, Halichondriidae) from Dok-do. Issue 1 (2nd January 2019) - Kim, Hana; Kang, Dong Won; Yu, Cheol; Jung, Yun Hwan; Yoon, Moongeun; Kim, Hyung June
Abstract: The mitogenome sequence of Halichondria sp. was determined for the first time in this study. Specimens were identified as a new species belonging to genus Halichondria and more detailed taxonomic study is ongoing. Circular complete mitogenome is 19, 687 bp in length, containing 14 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), and 25 transfer RNAs (tRNAs). Nucleotide composition of mitogenome consists of 28.9% A, 15.1% C, 21.9% G, 34.1% T, revealing high content of A + T similar to the other Suberitid sponges. Results will be useful for inferring phylogenetic relationships among the members of Halichondriid.